An Overview on Fecal Branched Short-Chain Fatty Acids Along Human Life and as Related With Body Mass Index: Associated Dietary and Anthropometric Factors - Rios-Covian, David; González, Sonia; Nogacka, Alicja M.; Arboleya, Silvia; Salazar, Nuria; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G. (Frontiers in Microbiology, 2020)
Short chain fatty acids (SCFA) are the main bacterial products of the catabolism of carbohydrates and proteins in the gut, and their role is essential in host-microbiota interactions. Acetic, propionic and butyric acids are the major SCFA produced in the gut, and they have been extensively studied. In contrast, branched short chain fatty acids (BCFA), mainly isovaleric and isobutyric acids, are produced in less amounts and their fecal levels in different human groups, intestinal microbial producing populations, and influence on health are insufficiently known. They have been proposed as markers of protein fermentation, which leads to the concomitant production of other fermentation products that can be harmful for the colon epithelium. In this context, the aim of this study was to shed light into the production of BCFA by the human intestinal microbiota, as related to age, body mass index (BMI) and diet. Fecal levels of the different SCFA were analyzed by gas chromatography in 232 healthy individuals with ages comprised between 3 months and 95 years, and BMI in adults ranging from 19 to 54. Dietary assessments in adults were obtained through a food frequency questionnaire. BCFA levels in feces were strongly and positively related with aging. However, not a significant relationship was obtained between BCFA and BMI. A negative correlation was found between the consumption of dietary insoluble fiber and fecal levels of BCFA. More studies are needed for improving our understanding on the relationship of BCFA production profile with the intestinal microbiota composition and human health.